The effect of implementing management functions in improving employee performance at the office of pt. Indonesian telecommunications (tbk) Makassar city - Risma wati (Institute of Accounting Research and Novation (IARN), 2021)
One of the factors that determine the achievement of company performance and organizational goals, human resources. In achieving organizational goals, human resources are very important to develop. The purpose of this research is to find out and analyze the effect of implementing management functions in improving employee performance at PT. Telecommunications Indonesia (Tbk) Makassar City. This research took place in Makassar City. While the data used in this study is employee data at PT. Telecommunications Indonesia (Tbk) Makassar City. As for data collection techniques, the distribution of questionnaires and observations at PT. Telecommunications Indonesia (Tbk) Makassar City. The analytical method used is a quantitative method. From the results of research on the Effect of Implementing Management Functions in Improving Employee Performance at PT. Telecommunications Indonesia (Tbk) Makassar City. Very influential on employee performance, namely reaching 80%, with the influence equation Y = 19.582 and 0.354 X, has a positive and significant influence or relationship with employee performance. The positive and significant influence indicates that there is a unidirectional influence between the variables of management functions and employee performance variables. Unidirectional influence here means that if the variables of management functions are low then it will be followed by low employee performance, and vice versa, if the application of management functions is high then it will be followed by high employee performance as well.